PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. NINJA XPRESS CABANG BATURAJA - Widayat, Agung; Rabiulkhri, Mailani; Herlina, Tati; Sari, Palupi Indah; Adrian Nova, Gitta Destalya (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2024)
This research aimed to determine the influence of work motivation and job satisfaction on employees’ performance at PT. Ninja Xpress Baturaja Branch. The data collection technique used in this research was through distributing questionnaires. The total population was 39 people. The data analysis technique used was Multiple Linear Regression. Based on the partial analysis results, there was a positive influence of work motivation on employees’ performance with a calculated t value of 2,264. The job satisfaction variable had a positive influence on employees’ performance with a calculated t value of 3,438. Simultaneously, it was found that there was an influence of work motivation and job satisfaction on employees’ performance at PT Ninja Xpress Baturaja Branch. The coefficient of determination (R2) obtained was 0.449. This showed that the contribution of the influence of work motivation and job satisfaction on employees’ performance was 44.90%, while the remaining 55.10% was influenced by other variables outside this research, namely knowledge, skills, abilities and attitudes that were not included in this research, for example abilities, improving results. achieved, work enthusiasm, self-development, quality and efficiency (Sutrisno, 2020:104).